Generalized Reflexive Structures Properties of Crossed Products Type (European Journal of Pure and Applied Mathematics, 2023)
Let $R$ be a ring and $M$ be a monoid with a twisting map $f : M × M → U(R)$ and an action map $ω : M → Aut(R)$. The objective of our work is to extend the reflexive properties of rings by focusing on the crossed product $R * M$ over $R$. In order to achieve this, we introduce and examine the concept of strongly $CM$-reflexive rings. Although a monoid $M$ and any ring $R$ with an idempotent are not strongly $CM$-reflexive in general, we prove that $R$ is strongly $CM$-reflexive under some additional conditions. Moreover, we prove that if $R$ is a left $p.q.$-Baer (semiprime, left $APP$-ring, respectively), then $R$ is strongly $CM$-reflexive. Additionally, for a right Ore ring $R$ with a classical right quotient ring $Q$, we prove $R$ is strongly $CM$-reflexive if and only if $Q$ is strongly $CM$-reflexive. Finally, we discuss some relevant results on crossed products.